Endoplasmic Reticulum Stress Regulates Scleral Remodeling in a Guinea Pig Model of Form-Deprivation Myopia - Chengcheng Zhu; Qingzhong Chen; Ying Yuan; Min Li; Bilian Ke (Journal of Ophthalmology)
Purpose. This study aimed to investigate the role of endoplasmic reticulum (ER) stress in scleral remodeling in a guinea pig model of form-deprivation myopia (FDM). Methods. Guinea pigs were form deprived to induce myopia. ER ultrastructural changes in the sclera were examined by transmission electron microscopy (TEM). The protein levels of ER stress chaperones, including GRP78, CHOP, and calreticulin (CRT), were analyzed by western blotting at 24 hours, 1 week, and 4 weeks of FD. Scleral fibroblasts from guinea pigs were cultured and exposed to the ER stress inducer tunicamycin (TM) or the ER stress inhibitor 4-phenylbutyric acid (4-PBA). CRT was knocked down by lentivirus-mediated CRT shRNA transfection. The expression levels of GRP78, CHOP, TGF-β1, and COL1A1 were analyzed by qRT-PCR or western blotting. Results. The sclera of FDM eyes exhibited swollen and distended ER at 4 weeks, as well as significantly increased protein expression of GRP78 and CRT at 1 week and 4 weeks, compared to the sclera of the control eyes. In vitro, TM induced ER stress in scleral fibroblasts, which was suppressed by 4-PBA. The mRNA expression of TGF-β1 and COL1A1 was upregulated after TM stimulation for 24 hours, but downregulated for 48 hours. Additionally, change of TGF-β1 and COL1A1 transcription induced by TM was suppressed by CRT knockdown. Conclusions. ER stress was an important modulator which could influence the expression of the scleral collagen. CRT might be a new target for the intervention of the FDM scleral remodeling process.